PENGARUH ASOSIASI MEREK, PERSEPSI KUALITAS DAN GAYA HIDUP TERHADAP MINAT BELI SANDAL DAN SEPATU BATA CABANG KUNINGAN - Riska Latipah (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2017)
This study against the background by increasing the competition in the industry sandals and shoes inIndonesia. This affects the sales of sandals and shoes Bata. This study also aims to analyze and test the effect of brandassociation, perceived quality and lifestyle of purchase intention Bata sandals and shoes Kuningan branch. Then analysisof data obtained using quantitative and qualitative analysis. Quantitative analysis includes: validity and reliability, datanormality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple regression analysis, hypothesistesting through t test and F, as well as the coefficient of determination (R ²). Qualitative analysis is the interpretationof the data obtained in the study and the results of data processing that has been carried out by members of descriptionand explanation. Hypothesis testing using t test showed that the variables of brand association and perceived quality issignificantly positive effect on purchase intention. Figures adjusted R2 of 0.585 indicates that 58.5% variable purchaseintention can be explained by the three independent variables in the regression equation. While the rest of 41.5% isexplained by other variables outside three variables used in this study.